Nuclear magnetic resonance spectroscopy-based metabolite profiling of transgenic tomato fruit engineered to accumulate spermidine and spermine reveals enhanced anabolic and nitrogen-carbon interactions. - Mattoo, A; Sobolev, A; Neelam, A; Goyal, R; Handa, A; Segre, A (2006)
Polyamines are ubiquitous aliphatic amines that have been implicated in myriad processes, but their precise biochemical roles are not fully understood. We have carried out metabolite profiling analyses of transgenic tomato (Solanum lycopersicum) fruit engineered to accumulate the higher polyamines spermidine (Spd) and spermine (Spm) to bring an insight into the metabolic processes that Spd/Spm regulate in plants. NMR spectroscopic analysis revealed distinct metabolite trends in the transgenic and wild-type/azygous fruits ripened off the vine. Distinct metabolites (glutamine, asparagine, choline, citrate, fumarate, malate, and an unidentified compound A) accumulated in the red transgenic fruit, while the levels of valine, aspartic acid, sucrose, and glucose were significantly lower as compared to the control (wild-type and azygous) red fruit. The levels of isoleucine, glucose, gamma-aminobutyrate, phenylalanine, and fructose remained similar in the nontransgenic and transgenic fruits. Statistical treatment of the metabolite variables distinguished the control fruits from the transgenic fruit and provided credence to the pronounced, differential metabolite profiles seen during ripening of the transgenic fruits. The pathways involved in the nitrogen sensing/signaling and carbon metabolism seem preferentially activated in the high Spd/Spm transgenics. The metabolite profiling analysis suggests that Spd and Spm are perceived as nitrogenous metabolites by the fruit cells, which in turn results in the stimulation of carbon sequestration. This is seen manifested in higher respiratory activity and up-regulation of phosphoenolpyruvate carboxylase and NADP-dependent isocitrate dehydrogenase transcripts in the transgenic fruit compared to controls, indicating high metabolic status of the transgenics even late in fruit ripening.